Pengaruh Beauty Influencer dan Instagram Marketing Terhadap Brand Awareness Mother of Pearl - Azhari, Reny; Amali, Muhammad Thoyib (Jurnal Pustaka Komunikasi, 2025)
Beauty has become an essential aspect of human life along with shifting social trends and the rapid growth of the cosmetics industry. Today, beauty products not only serve to enhance appearance but also act as a profound means of self-expression. The rise of social media has further transformed the landscape of the cosmetics industry, creating new opportunities for marketing strategies and brand communication. Based on this phenomenon, this study aims to examine the influence of Tasya Farasya as a beauty influencer on Mother of Pearl’s brand awareness, the influence of Instagram marketing as a promotional medium on Mother of Pearl’s brand awareness, as well as the combined influence of beauty influencer and Instagram marketing on Mother of Pearl’s brand awareness. This research adopts a quantitative approach by surveying 100 beauty enthusiasts who follow Tasya Farasya or Mother of Pearl on Instagram. The collected data were analyzed using multiple linear regression with hypothesis testing conducted both partially and simultaneously. The findings indicate that Tasya Farasya, as a beauty influencer, has a positive and significant effect on Mother of Pearl’s brand awareness. In contrast, Instagram marketing alone does not significantly affect brand awareness. However, when combined, beauty influencer and Instagram marketing positively and significantly influence Mother of Pearl’s brand awareness.